Spiritualism in the history of Russian philosophical thought: key assesments and prospects - Vladislav Razdyakonov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
The article presents a critical review of the assessments of Modern Spiritualism in Russian philosophical historiography and positions it as a certain kind of natural theology. The author positions spiritualism as a special religious philosophy and outlines the reasons why it was considered as a practice without any philosophical significance. The article considers philosophical characteristics of Spiritualism given by Russian religious philosophers and offers some critical remarks on historiography's opinion about Spiritualism as a kind of "positivism". The author suggests, that spiritualism should be investigated in the perspective of the history of philosophical and theological thought of the early New Modern period. The article deals with analogies between the themes of early modern natural theology and the problems spiritualists were deeply interested in. It touches upon the discussions about the nature of the soul, especially, the questions of its corporeality and possible annihilation. Early modern discussions about witchcraft should be studied as a key issue, which links natural theology and spiritualism. The article proposes to compare seventeenth-century "witch-hunts", aimed to prove the existence of the spirit world, and nineteenth-century investigations of mediums. The importance of Leibnizianism and pneumatological teachings of the eighteenth century as precursors of spiritualist religious and philosophical thought is also pointed out. The article proposes to investigate Spiritualism not only as a subject for Orthodox apologetics’ criticism, but also as a special kind of Christian apologetics that emerged in the early Modern period and aimed at proving the immortality of the soul while refuting the arguments of materialist critics. Both Russian spiritualists and Russian philosophers (V.S. Soloviev, N.Y. Grot, L.M. Lopatin) were interested in "mediumistic phenomena". It is argued that the spiritualists of the late 19th century sought to overcome «positivist» limitations, and were not satisfied with the Kantian solution, which put a barrier to the cognition of the "real" world. The study of Spiritualism in the perspective of Christian natural theology makes it possible to grasp the main reason for the interest of Russian philosophers in Spiritualism and its’ "psychic phenomena" – the potential opportunity to find new arguments in favor of the immortality of the soul.